2000
DOI: 10.1042/bj3480425
|View full text |Cite
|
Sign up to set email alerts
|

Increase of mitochondria and mitochondrial DNA in response to oxidative stress in human cells

Abstract: Mitochondrial respiratory function is impaired in the target tissues of patients with mitochondrial diseases and declines with age in various human tissues. It is generally accepted that respiratory-chain defects result in enhanced production of reactive oxygen species and free radicals in mitochondria. Recently, we have demonstrated that the copy number of mitochondrial DNA (mtDNA) is increased in the lung tissues of elderly human subjects. The mtDNA copy number was suggested to be increased by a feedback mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(101 citation statements)
references
References 29 publications
6
93
1
1
Order By: Relevance
“…The net effect of OXA treatment at the mitochondrial level was increased succinate dehydrogenase (SDH) content within the muscle, indicative of a greater mitochondrial oxidative capacity. However, there was a trend for OXA ( p = 0.07) to reduce mitochondrial viability relative to VEH (Figure 8C), highlighting that the innate response to oxidative stress and/or mitochondrial toxicity is to increase the total pool to preserve energy production capacity (Hsin-Chen et al, 2000) as indicated by more intense SDH staining (Figure 6C) and mitochondrial density (Figure 8C). Consistent with this finding, a marked increase in mtROS production was detected in FDB fibers following OXA treatment (Figure 8B) giving further support to our theory that mitochondrial biogenesis could be increased in order to accommodate oxidative stress and a dysfunctional mitochondrial population (Hsin-Chen et al, 2000; Kujoth et al, 2005; Stowe and Camara, 2009; Sorensen et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The net effect of OXA treatment at the mitochondrial level was increased succinate dehydrogenase (SDH) content within the muscle, indicative of a greater mitochondrial oxidative capacity. However, there was a trend for OXA ( p = 0.07) to reduce mitochondrial viability relative to VEH (Figure 8C), highlighting that the innate response to oxidative stress and/or mitochondrial toxicity is to increase the total pool to preserve energy production capacity (Hsin-Chen et al, 2000) as indicated by more intense SDH staining (Figure 6C) and mitochondrial density (Figure 8C). Consistent with this finding, a marked increase in mtROS production was detected in FDB fibers following OXA treatment (Figure 8B) giving further support to our theory that mitochondrial biogenesis could be increased in order to accommodate oxidative stress and a dysfunctional mitochondrial population (Hsin-Chen et al, 2000; Kujoth et al, 2005; Stowe and Camara, 2009; Sorensen et al, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…However, there was a trend for OXA ( p = 0.07) to reduce mitochondrial viability relative to VEH (Figure 8C), highlighting that the innate response to oxidative stress and/or mitochondrial toxicity is to increase the total pool to preserve energy production capacity (Hsin-Chen et al, 2000) as indicated by more intense SDH staining (Figure 6C) and mitochondrial density (Figure 8C). Consistent with this finding, a marked increase in mtROS production was detected in FDB fibers following OXA treatment (Figure 8B) giving further support to our theory that mitochondrial biogenesis could be increased in order to accommodate oxidative stress and a dysfunctional mitochondrial population (Hsin-Chen et al, 2000; Kujoth et al, 2005; Stowe and Camara, 2009; Sorensen et al, 2016). Remarkably, BGP-15 completely protected against the OXA-induced increase in mtROS production and reduction in FDB fiber diameter and intramuscular protein content, however, this effect was independent from any modulation of protein synthesis, atrophy, autophagy or apoptosis markers measured in our study (Figure 9).…”
Section: Discussionmentioning
confidence: 92%
“…The mtDNA synthesis can be stimulated by mild oxidative stress, resulting in an increase of mtDNA copy number to supply energy for cell survive, while immoderate oxidative stress may lead to decrease in mtDNA synthesis because of defect mitochondria and result in apoptosis and cell death [30, 35]. Since the median particle concentration in our study (1.1 mg/m 3 ) is not very high (the occupational exposure limit is set as 5 mg/m 3 by the Swedish Work Environment Authority [28]), we concluded that the increase in RmtDNAcn could be a feedback response to compensate defect mitochondria with an impaired respiratory chain, or mutated mtDNA caused by oxidative damage from welding fume [18, 35]. The methylation level change in the D-loop could be another molecular event related to particle induced oxidative stress, which can damage methylation of nucleotides [36].…”
Section: Discussionmentioning
confidence: 99%
“…The copy numbers of mtDNA vary in each mitochondrion, as well as in different cells, different tissues and individuals. Alteration of mtDNA copy number has been observed as a response to oxidative stress in vitro and in vivo [1820]. Moreover, integrity of the mitochondrial genome can affect mitochondrial function [21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the inconsistent reports, oxidative stress caused by mitochondria is shown to be involved in the regulation of mitochondrial transcription and proliferation with complicated compensatory mechanism (34)(35)(36). In SARS, both pathogen and host factors are considered to be important for the pathogenesis (9).…”
Section: Discussionmentioning
confidence: 99%